Quality of life of Brazilian plastic surgeons - Guilherme Frederico Ferro Alves; Saulo Mendes Sobreira; André Dias Coni; Catherine Maureira Oyharçabal; Thiago Sipas Teixeira Luz; Marcio Yuri de Souza Ferreira; Ricardo Jean Bertinatto; Denis Valter Calazans Loma (Revista Brasileira de Cirurgia Plástica)
Introduction: Medical quality of life (QoL) is an international object of study. Brazilian Plastic Surgeons QoL hasn`t yet been assessed, with few studies to perform any evaluation on the subject or estimate variables involved. Methods: This is a transversal, non-comparative, non-experimental, contemporary and of full selection study. An on-line research was performed between July and December in 2021, through the WHOQOL-bref questionnaire application, added with social-demographic information. The population will be composed of plastic surgery residents and surgeons associated with the Brazilian Society of Plastic Surgery (SBCP). Results: We obtained 168 answers via Google Forms®, which allowed us to determine our population through social- demographic questionnaire and make associations with the WHOQOL-bref findings. Conclusion: The current study identified correlations between sociodemographics and quality of life of the Brazilian plastic surgeon. We bring forward descriptive data on a subpopulation of responders inside the SBCP, which achieved a score positively higher than 50% in all of the questionnaire domains.